Atti dell' Accademia romanistica constantiniana. Universitá degli Studi di Perugia. Facoltá di Giurisprudenza, 1986, 453 pp. - Hubeñak, Florencio (2000)
Fil: Hubeñak, Florencio. Pontificia Universidad Católica Argentina. Facultad de Derecho; Argentina